Reorganization of inter‐chromosomal interactions in the 2q37‐deletion syndrome. (19th June 2018) - Maass, Philipp G; Weise, Anja; Rittscher, Katharina; Lichtenwald, Julia; Barutcu, A Rasim; Liehr, Thomas; Aydin, Atakan; Wefeld‐Neuenfeld, Yvette; Pölsler, Laura; Tinschert, Sigrid; Rinn, John L; Luft, Friedrich C; et al.
Abstract: Chromosomes occupy distinct interphase territories in the three‐dimensional nucleus. However, how these chromosome territories are arranged relative to one another is poorly understood. Here, we investigated the inter‐ chromosomal interactions between chromosomes 2q, 12, and 17 in human mesenchymal stem cells (MSCs) and MSC‐derived cell types by DNA‐FISH. We compared our findings in normal karyotypes with a three‐generation family harboring a 2q37‐deletion syndrome, featuring a heterozygous partial deletion of histone deacetylase 4 ( HDAC4 ) on chr2q37. In normal karyotypes, we detected stable, recurring arrangements and interactions between the three chromosomal territories with a tissue‐specific interaction bias at certain loci. These inter‐ chromosomal interactions were confirmed by Hi‐C. Interestingly, the disease‐related HDAC4 deletion resulted in displaced inter‐ chromosomal arrangements and altered interactions between the deletion‐affected chromosome 2 and chromosome 12 and/or 17 in 2q37‐deletion syndrome patients. Our findings provide evidence for a direct link between a structural chromosomal aberration and altered interphase architecture that results in a nuclear configuration, supporting a possible molecular pathogenesis. Synopsis: DNA‐FISH and Hi‐C allow for in‐depth analysis of the formation and dynamics of inter‐chromosomal contacts in human cells. A genetic deletion linked to human disease causes displacement of interactions that may contribute to the disease phenotype. Non‐homologous inter‐chromosomal contacts (NHCCs) of chromosomal territories 12 and 17 are stable across different tissues. Locus‐specific NHCCs exist and appear to be tissue‐specific. Chromosomal aberrations (e.g. HDAC4 locus deletion) can lead to displaced NHCCs. Inter‐chromosomal Hi‐C analysis reveals that inter‐chromosomal contacts are preserved across cell‐types. Abstract : DNA‐FISH and Hi‐C reveal the formation and dynamics of inter‐chromosomal contacts in human cells and show that disease‐linked chromosome aberrations can alter the configuration of such contacts.